Implikasi Akta Perjanjian Pranikah dalam Upaya Perlindungan Suami Istri guna Kepentingan Pembagian Harta Bersama akibat Perceraian - Risky Risky; Isnina Isnina; Tengku Erwinsyahbana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Marriage is a physical and emotional bond between a man and a woman recognized by law and religion. In practice, issues often arise regarding the status of joint property acquired during marriage, especially in the event of divorce. To anticipate such disputes, a prenuptial agreement serves as a legal instrument that provides certainty and legal protection for both husband and wife in managing and dividing joint assets, either during the marriage or after divorce. This study aims to analyze the urgency of drafting a prenuptial agreement, identify the legal aspects that need to be included in the deed, and examine its juridical implications. This research employs a normative legal method with a conceptual and statutory approach, using descriptive-analytical techniques, secondary data sources, and qualitative analysis. The findings indicate that a prenuptial agreement has significant urgency in protecting the rights of both spouses in case of divorce. Furthermore, it holds binding legal force and creates juridical implications by clarifying the separation between personal and joint property, thereby ensuring legal certainty for both parties.